In situ stress measurements on thin film Au positive electrode during the first discharge of Li-O2 batteries - Dykes H.; Rosy; Sharon D.; Noked M.; Çapraz Ö. (My University, 2025)
The formation and growth of the Li2O2 discharge product impacts the reversibility of the oxygen evolution and reduction reactions in Li-O2 batteries which may lead to a shorter cycle life. A clear understanding of the surface reactions and the growth mechanism of Li2O2 requires probing dynamic changes on the surface of the positive electrodes in situ during the discharge of a Li-O2 battery. To investigate this, we establish an experimental system by adopting a multi-beam optical sensor (MOS) and developing a custom-made battery cell. First, the accuracy and reliability of the system was demonstrated by analyzing the stress accumulation on the Au negative electrode during Li plating/stripping, and the results were consistent with an earlier single-beam scanning deflectometry report. Then, the Li-O2 battery was discharged in LiNO3 in diglyme electrolyte by applying either linear sweep voltammetry or by applying constant current under an O2 environment. Control experiments in Argon-saturated electrolytes indicate surface stress generation due to charge-induced stress. The stress generation on Au positive electrode is attributed to the formation of Li2O2 reaction products on the Au surface and charge-induced stress. © 2021 The Author(s).